Metody oceny społecznych aspektów działalności przedsiębiorstw użyteczności publicznej na przykładzie zakładu wodociągów i kanalizacji - Głuszczuk, Dariusz (Assessment Methods of Social Aspects od Activities of Public Utility Companies on the Example of a Waterworks and Sewage Plant, 2008)
The assessment of social aspects of activities of public utility companies involves solving some I fey problems, which can be contained in two questions: How to measure the degree of need satisfaction within municipalities? What determines the objectivization of formulated opinions? Attempts to answer these questions in the article lead to the general systematics and presentation of methods that can measure the degree of need satisfaction within municipalities in relation to waterworks and sewage services, a discussion on the objectiveness of formulated opinions, and a proposal of statistical and psychological research. The author believes that survey techniques enrich and make statistical measuring of the degree of satisfaction of people's collective needs more objective. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 374-383